2013
DOI: 10.4028/www.scientific.net/amr.797.401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Permanent Magnet Excitation on Material Removal Rate in Area Taking Magnetorhelogical Finishing

Abstract: In this paper, a novel area taking MRF process using permanent magnet as excitation was proposed. Four types of permanent magnet configurations were considered. Polishing experiment was conducted. Effects of different permanent magnet configurations on material removal rate (MRR) were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…At present, there are various types of MRF devices, such as groove type [25], wheel type [25], belt type [246,247], disk type [248,249], cluster type [250,251], ball head type [252,253], etc, which are suitable for surface processing of various types and sizes, such as plane, concave, convex, inner surface, etc. The diameter of the polished workpiece is mostly more than 100 mm or even 1 m. The research status and characteristics comparison of MRF devices are shown in table 6.…”
Section: Magnetorheological Finishingmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are various types of MRF devices, such as groove type [25], wheel type [25], belt type [246,247], disk type [248,249], cluster type [250,251], ball head type [252,253], etc, which are suitable for surface processing of various types and sizes, such as plane, concave, convex, inner surface, etc. The diameter of the polished workpiece is mostly more than 100 mm or even 1 m. The research status and characteristics comparison of MRF devices are shown in table 6.…”
Section: Magnetorheological Finishingmentioning
confidence: 99%
“…After optimizing the process parameters, it was found that the surface roughness of BK7 glass could be reduced to 3.8 nm. Yin et al [248,249] explored the material removal rate under the influence of permanent magnet configurations by using a disc type MRF device, as depicted in figure 33(b). Permanent magnets of different configurations are placed under the polishing disc and form a gradient magnetic field distribution.…”
Section: Stainless Steelmentioning
confidence: 99%